The Effectiveness of Reading Interventions for English Learners: A Research Synthesis. (January 2016) - Richards-Tutor, Catherine; Baker, Doris L.; Gersten, Russell; Baker, Scott K.; Smith, Jeanie Mercier
This article reviews published experimental studies from 2000 to 2012 that evaluated the effects of providing reading interventions to English learners who were at risk for experiencing academic difficulties, including students with learning disabilities. Criteria included: (a) the study was published in a peer-referred journal, (b) the study was an intervention for English learners at risk or with a learning disability in Grades K–12, (c) data were disaggregated by English learner status if all participants were not English learners, and (d) information about fidelity of implementation was reported. Twelve studies met these criteria. Results of seven studies conducted in kindergarten and first grade indicated significant moderate-to-large effect sizes (ES range, 0.58–0.91) for interventions targeting beginning reading skills. Findings in five of the 12 studies suggested significant moderate-to-large effects in reading or listening comprehension (ES range, 0.47–2.34). The interventions in these studies included explicit instruction, and 10 used published intervention programs. Moderator variables, such as group size, minutes of intervention, and type of personnel delivering the intervention, were not significant predictors of outcomes.